Indiscriminate use of Ritalin® by students of a College Southwest Goiano (Research, Society and Development, 2022)
Ritalin® is a drug that acts directly on the Central Nervous System (CNS), it is indicated for the treatment of Attention Deficit Hyperactivity Disorder (ADHD) in children and adults, however its consumption has increased in the academic environment which is directly related to the psychostimulant benefits that the substance ensures. The medication should only be used under medical supervision because it is of controlled use, which can cause dependence and long-term damage. Objective: To analyze the knowledge of students at a college in the southwest of Goiás about the indiscriminate use of Ritalin®. Method: This is a quantitative, exploratory field research to analyze the students' knowledge about the indiscriminate use of Ritalin®. A questionnaire containing 20 questions was applied to the students of the following courses: Law, Nursing, Pharmacy, Physiotherapy, Medicine, Nutrition, Dentistry and Psychology in a College of the Southwest of Goias, Brazil - through GoogleForms by a link available via WhatsApp. Results: Among the most relevant data, 15.3% (n=48) of the participating students affirmed the use of the drug, and 75% (n=36) used it without the prescription of the professional with the purpose of improving the concentration on the eve of evaluations. Conclusion: This study showed that the use of Ritalin is minimal in relation to the number of participating students, and the individuals who use it claimed to be by recommendation of friends. Evidencing that students resort to the drug as a "miracle pill".